Beobachtungen zum Kompositionstyp Substantiv + freundlich im Vergleich mit dem Polnischen - Koniuszaniec, Gabriela (Wydawnictwo Naukowe UAM, 1989)
The subject of considerations in this article is a word formation consisting of a noun and an adjective "freundlich". Compounds of this type, characteristic mainly of the German language, occur most often in the press. The material base in this article are data stored in the Mannheim corpus and examples derived from West German press. The above mentioned compounds were analysed in respect of morphology, syntax and semantics. Contrastive study showed that these compounds do not have formally their analogical equivalent in Polish. That is why they are expressed in Polish either by means of negation, or less frequently as adjectives or adverbs.